JAVMA News (Journal of the American Veterinary Medical Association, 2013)
Objective To summarize owner-reported recurrence of clinical signs consistent with thoracolumbar intervertebral disk herniation in dogs treated by intradiskal injection of chondroitinase ABC (ChABC) and to compare recurrence rate versus routine surgical management. Methods This pragmatic retrospective, time-matched cohort comparison study included 2 groups of dogs that recovered independent locomotion (> 50 unsupported steps) following treatment between October 2022 and March 2025 for acute nonambulatory paraparesis or paraplegia, assumed or proven to be caused by intervertebral disk herniation, with (1) 1.25-U ChABC injections into 4 consecutive intervertebral disks targeted on the basis of neurologic examination or (2) routine decompressive surgery following cross-sectional imaging. Recurrent clinical signs were reported retrospectively to investigators. Results The study population consisted of 47 ChABC-treated dogs and 79 surgical cases with similar demographics. Fenestration number in the surgery group was variable (7 dogs had 0 fenestrations, 32 dogs had 1, 17 dogs had 2, 20 dogs had 3, and 3 dogs had an unknown number). Recurrence occurred in 24 of 79 surgical dogs (30%) compared to 6 of 47 ChABC-treated dogs (13%). Univariable Poisson regression demonstrated a significantly lower recurrence rate in the ChABC group (incidence rate ratio [IRR], 0.38; 95% CI, 0.17 to 0.87) and in older dogs (IRR, 0.81; 95% CI, 0.70 to 0.93). The optimized multivariable model included both these variables and suggested that ChABC injections were associated with an adjusted recurrence incidence rate reduction of approximately 70%. Conclusions Multidisk injection of ChABC was associated with a reduced rate of owner-reported recurrence of clinical signs suggestive of intervertebral disk herniation compared to surgery. Clinical relevance Intradiskal injection of ChABC may be an effective prophylactic against intervertebral disk herniation.